2021
DOI: 10.1038/s41467-021-25842-7
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the actin nucleation promoting factor WASp provides a therapeutic approach for hematopoietic malignancies

Abstract: Cancer cells depend on actin cytoskeleton rearrangement to carry out hallmark malignant functions including activation, proliferation, migration and invasiveness. Wiskott–Aldrich Syndrome protein (WASp) is an actin nucleation-promoting factor and is a key regulator of actin polymerization in hematopoietic cells. The involvement of WASp in malignancies is incompletely understood. Since WASp is exclusively expressed in hematopoietic cells, we performed in silico screening to identify small molecule compounds (SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 114 publications
0
9
0
Order By: Relevance
“…However, cortactin was not yet reported as a potential drug target, neither in cancer nor in bacterial pathogenesis. Nevertheless, a recent study reported about a promising new approach for the treatment of specific hematopoietic malignancies by targeting WASP-mediated signaling (Biber et al, 2021).…”
Section: Outlook and Per S Pec Tive Smentioning
confidence: 99%
See 1 more Smart Citation
“…However, cortactin was not yet reported as a potential drug target, neither in cancer nor in bacterial pathogenesis. Nevertheless, a recent study reported about a promising new approach for the treatment of specific hematopoietic malignancies by targeting WASP-mediated signaling (Biber et al, 2021).…”
Section: Outlook and Per S Pec Tive Smentioning
confidence: 99%
“…However, cortactin was not yet reported as a potential drug target, neither in cancer nor in bacterial pathogenesis. Nevertheless, a recent study reported about a promising new approach for the treatment of specific hematopoietic malignancies by targeting WASP‐mediated signaling (Biber et al, 2021). The authors discovered a small molecule compound that binds WASP and promotes its degradation, thus inhibiting key WASP‐dependent actin processes in hematopoietic cancer cells in vitro and in vivo without affecting naïve, healthy cells.…”
Section: Outlook and Perspectivesmentioning
confidence: 99%
“…This indicates that the protection of the ubiquitination residues (K76 and K81, Figure 2) may be a good target to reduce WASp degradation long enough to restore cell functionality. On the other hand, a small molecule that interferes with the WIP‐WASp interaction at the WH1 domain, thereby exposing WASp to degradation may be useful to treat specific hematopoietic malignancies since the abolished WIP‐WASp interaction results in reduced cell proliferation, migration, and invasiveness 112 …”
Section: Mechanistic Insight For Therapeutic Benefitmentioning
confidence: 99%
“…On the other hand, a small molecule that interferes with the WIP-WASp interaction at the WH1 domain, thereby exposing WASp to degradation may be useful to treat specific hematopoietic malignancies since the abolished WIP-WASp interaction results in reduced cell proliferation, migration, and invasiveness. 112 Due to the fact that the activation of WASp is regulated by its structural conformation, more studies focusing on its active/inactive and spatial localization status may be beneficial not only for the patients but also in the context of other applications such as engineering T/NK cells with to increase their cytotoxic activity as shown for XLN patient NK cells and T cells.…”
Section: Mutationsinwas/xlt/xlnaffectwasp Stability and Autoinhibitionmentioning
confidence: 99%
“…The small molecule wiskostatin inhibits WASp by inducing folding of the GBD into its autoinhibited conformation stabilizing WASp into its autoinhibited conformation 30 . Another reported compound (SMC#13) promotes WASp degradation and has anti-tumor activity in lymphoma and leukemia models 31 . Thus, small molecules may mimic the effects of WASp mutants and selectively lead to cell death in hematological lineages, indicating WASp as a new target not yet explored in the clinical setting.…”
Section: Introductionmentioning
confidence: 99%